Towards Autonomous, Adaptive, and Context-Aware Multimodal Interfaces: Theoretical and Practical Issues Third COST 2102 International Training School, Caserta, Italy, March 15-19, 2010, Revised Selected Papers - Esposito, Anna; Esposito, Antonietta M.; Martone, Raffaele; Müller, Vincent; Scarpetta, Gaetano (Information Systems and Applications, incl. Internet/Web, and HCI, 2011)
This volume brings together the advanced research results obtained by the European COST Action 2102: "Cross Modal Analysis of Verbal and Nonverbal Communication". The research published in this book was discussed at the 3rd jointly EUCOGII-COST 2102 International Training School entitled "Toward Autonomous, Adaptive, and Context-Aware Multimodal Interfaces: Theoretical and Practical Issues ", held in Caserta, Italy, on March 15-19, 2010. The book is arranged into two scientific sections. The 18 revised papers of the first section, "Human-Computer Interaction: Cognitive and Computational Issues", deal with conjectural and processing issues of defining models, algorithms, and strategies for implementing cognitive behavioural systems. The second section, "Synchrony through Verbal and Nonverbal Signals", presents 21 revised lectures that provide theoretical and practical solutions to the modelling of timing synchronization between linguistic and paralinguistic expressions, actions, body movements, activities in human interaction and on their assistance for an effective communication.